Assessment and Management of Psychosocial Needs: Social Work Utilization in Comprehensive Cleft Team Care. (September 2018) - Kaye, Alison; Lybrand, Sandra; Chew, William L.
Objective: To determine family-reported psychosocial stressors and social worker assessments and interventions within a comprehensive cleft team. Design: Single-institution prospective provider-completed survey. Patients: Four hundred one families seen by cleft team social worker over a 7-month period. Results: Most families (n = 331; 83%) participated in the team social work assessment. At least 1 active psychosocial stressor was reported by 238 (72%) families, with 63 (19%) families reported 3 or more stressors. There were 34 types of stressors reported. Most common were financial strain, young age of patient, new cleft diagnosis, and distance from clinic (57% of families live over an hour away). Family structure and home environment were assessed in detail for 288 (87%) families. Detailed assessments for access to care and behavioral/developmental issues also figured prominently. Social work interventions were provided in 264 (80%) of the visits, of which 91 were for families of new patients with over half who had infants less than 3 months old. Of the 643 interventions provided, the most frequent were parent mental health screens and counseling, early intervention referrals, transportation assistance, securing local hotel discounts, orthodontic referrals, and orthodontic cost coverage. Approximately 10% of encounters required follow-up contact related to the psychosocial concerns identified in clinic. Conclusions: The inclusion of a cleft team social worker is a critical component of comprehensive cleft team care as evidenced by the large proportion of families who required assistance. Ongoing social work assessments are recommended for each patient to help address the variety of psychosocial stressors families face.